And the ocean was our sky - Ness, Patrick, 1971-; Rovina, Cai (New York, NY : HarperTeen, an imprint of HarperCollinsPublishers, 2018)
A proud warrior whale pod hunts the mythical Toby Wick, a man with a white ship who kills whales and men, but their final, vengeful hunt will change the worlds of both species forever.
Keywords: Whales -- Fiction; Human-animal relationships -- Fiction; Revenge -- Fiction; Quests (Expeditions) -- Fiction